Assessment of an educational strategy and application of an oral health preventive protocol in early childhood (2020)
ABSTRACT Introduction: in Colombia, educational and preventive strategies to improve oral health in early childhood have been developed, but few evaluative studies have been conducted to assess their results. The aim of this study was to assess the knowledge on early childhood oral care acquired by education agents after participating in an educational strategy, and to evaluate the results of the implementation of the Ministry of Health’s preventive protocol “I am a more smiling generation” (Soy una generación más sonriente). Methods: this was a mixed-focus study. The qualitative component was a participatory assessment of learning. It involved 45 education agents registered in a state program, who participated in workshops and focus groups. The quantitative component was a longitudinal study with the participation of 54 mother-child pairs belonging to the same program. The preventive protocol was applied three times over a twelve-month period. It included educational reinforcement and application of fluoride varnish to the children, using oral examination and assessment of their dental caries risk, as well as a survey to identify the families’ social conditions. Results: after applying the preventive protocol, the average carious teeth in children decreased from 3.1 teeth in the first examination to 2.2 in the third one. Prior to application of the preventive protocol, 49% of children had a high risk of developing cavities and in the last visit 63% were at low risk while 5.6% were at high risk. A number of positive aspects result from this learning assessment, including the adoption of new pedagogical strategies to accompany children during oral care practices; there are also some aspects to improve in relation to the persistence of conflicting knowledge concerning children’s rights to oral health. Conclusion: following the application of the preventive protocol, the children’s average carious teeth decreased, as well as their risk for dental caries. Educational agents acquired new knowledge, but uniform knowledge in terms of children’s health rights is still lacking.